Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Lentera Bahari Putra Mas: The Influence of Leadership Style and Work Environment on Employee Performance at PT Lentera Bahari Putra Mas - Nanda Purvitasani; Viani Naufalia (CV Warnak Johanna Nusantara, 2026)
This study is based on the importance of human resources in supporting the achievement of organizational goals, where employee performance is influenced by effective leadership and a conducive work environment. The objective of this research is to analyze the effect of leadership style and work environment on employee performance at PT Lentera Bahari Putra Mas. This study employs a quantitative research method. The population and sample consist of 45 employees, therefore the sampling technique used is saturated sampling. Data analysis was conducted using data quality tests, classical assumption tests, multiple linear regression analysis, t-test, f-test, and coefficient of determination with the assistance of SPSS version 27. The results indicate that leadership style has a significant effect on employee performance, with a t-value of 3.717 and a significance value of 0.001 < 0.05, contributing 63.5%. The work environment also has a significant effect on employee performance, with a t-value of 4.399 and a significance value of 0.000 < 0.05, contributing 66.58% and acting as the dominant variable. Simultaneously, leadership style and work environment have a significant effect on employee performance, as indicated by an F-value of 63.022 and a significance value of 0.000 < 0.05. The coefficient of determination value of 0.750 indicates that both variables explain 75% of the variation in employee performance. This conclusion confirms that employee performance improvement is influenced by appropriate leadership and a supportive work environment.